Analysis Of The Welfare Level Of Fishermen in Klampis Village, Klampis District, Bangkalan Regency - Qomariyah, Badriyatul; Hamidah Hendrarini; Nisa Hafi Idhoh Fitriana (Grouper, 2025)
Fishermen are one of the coastal community groups that are vulnerable to economic uncertainty due to dependence on catch results and natural factors. Weather fluctuations, price changes, and limited access to production facilities often affect their income and welfare. In Klampis Village, the increase in the number of fishermen has not been followed by an increase in fish catch, leading to economic problems within fishermen households. This study aims to analyze household income and fishermen's welfare based on the Fishermen's Exchange Rate (NTN) in Klampis Village, Klampis Subdistrict, Bangkalan Regency. The research uses a descriptive quantitative approach with 60 respondents selected through simple random sampling from a total population of 150 fishermen. The analytical methods used include household income analysis and NTN calculation. The results show that the average household income of fishermen is IDR 3,585,718 per month, while the average expenditure reaches IDR 3,498,426 per month. The NTN value of 1.024 indicates that fishermen households are at an economic equilibrium point, with a surplus that has not yet been utilized for savings or long-term investments. Most income is still allocated to daily consumption and operational costs, resulting in weak long-term economic resilience.